Lambda Ig constant region genes are translocated to chromosome 8 in Burkitt's lymphoma with t(8;22). - de la Chapelle, A (1983)
By in situ hybridization of normal human chromosomes with a cloned genomic probe specific for the constant region of the lambda immunoglobulin genes, band 22q11 was preferentially labelled. In two cell lines with t(8;22) derived from Burkitt's lymphoma a strong signal was noted on the 8q+ chromosome derivative, indicating that the constant region of the lambda Ig gene cluster was translocated from chromosome 22 to chromosome 8. In addition, the signal observed on the 22q- derivative chromosome was stronger than the background in one of the two cell lines tested, but not in the other. The implications are that the break point in chromosome 22 in some cases lies within the Ig gene itself or between clusters of such genes, and that different cases have different break points.